HUBUNGAN TEKNIK MENYUSUI DENGAN KELANCARAN PRODUKSI ASI IBU POST SECTIO CAESAREA (Studi di Ruang Mawar RSUD Mohammad Zyn Kab. Sampang) - Qurrotu aini; Merlyna Suryaningsih (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2021)
ABSTRACT Breastfeeding technique is a factor that plays an important role in breast production because the wrong breastfeeding technique will cause sore nipples and mothers are reluctant to breastfeed their children, if the baby is not breastfeeding it can affect the stimulation of breast production. Based on the results of a preliminary study in the Irna Mawar Room, RSUD Dr. Mohammad Zayn Sampang found that there were still many post partum mothers who experienced non-fluent breast milk as much as 90%. The purpose of this study is to analyze the relationship between breastfeeding techniques and the smooth production of breast milk in post SC mothers in the Rose Room of RSUD Mohammad Zyn. The design of this study was an analytic survey with a cross-sectional approach. The independent variable was the relationship between breastfeeding techniques and the dependent variable was the smooth production of breast milk. The population was 37 post sectio caesarea mothers with a sample of 27 respondents using purposive sampling. The study used a breastfeeding technique observation sheet and a questionnaire on the smoothness of breast milk production. Bivariate data analysis used Spearman Rank test. No. KEPK 445/643/434.203.100/2022 Based on the results of the study, it was found that breastfeeding techniques for post-sectio caesarea mothers were mostly good (88.9%), smooth breast production in post-sectio-cesarean mothers was almost entirely smooth (92.6%) and the results of the Spearman rank statistical test obtained p value (0.000) < α (0.05) which means that there was a strong relationship between breastfeeding technique and the smooth production of breast milk with a correlation value of 0.817. Based on the results of the study, it is hoped that health workers can educate mothers about correct breastfeeding techniques so that post sectio caesarea mothers can apply correct breastfeeding techniques to facilitate production.